Cumulative Image Encryption Approach - Das, R; Dutta, S (International Journal of Computer Sciences and Engineering, 2025)
Secret sharing scheme divides colour image into user defined N (positive integer) number of shares with different transference where decryption is being carried out by human visual system using at least K (positive integer) number of shares out of N number of shares. In image key encryption technique the user perform user define BWM&AS operation (bit wise masking and alternate sequence) in between two constitutive bits of each pixel of original image and image key. In this combined approach we introduce two level of encryption using secret sharing scheme followed by Image key encryption technique using BWM&AS operation. Firstly, the original image is encrypted using an image key then that encrypted image is being divided into N number of shares where each of the share is again being encrypted by unique image key in encryption end. In decryption end, we retrieve original shares from the encrypted shares using appropriate image key and generate the original encrypted image by taking K number of share out of N. Lastly, we retrieve the original image by performing BWM&AS operation between the original image key and encrypted image. Thus an attempt is made to enhance the security.